ANALISIS PENGAMBILAN KEPUTUSAN PENAMBAHAN INVESTASI AKTIVA TETAP - Djoko Maryanto (POLITEKNIK LP3I JAKARTA, 2019)
This study aims to find out and analyze the Accounting System for Receivables carried out by Fixed Assets Investment and to find out the obstacles faced by the implementation of the Accounts Receivable Accounting System. Research method applied in this research is associative method and method correlation by using data exposit facto. Data analytical technique applied is regression test and correlation beforehand does analysis clauses Normality test. Hypothesis test done with correlation coefficient formula product moment yielding r calculate = 0,953, so that with calculating determinant coefficient is known by addition of investment of plant asset equal to 90,9% while equal to 9,1% is addition at outside by investment Plant asset.Key words: Analysis, investment in plant asset, operating income